2017
DOI: 10.1177/1744806917710862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperbaric oxygen therapy on neuropathic pain via mitophagy in microglia

Abstract: PurposeHyperbaric oxygen (HBO) therapy has been suggested to palliate neuropathic pain, but the mechanisms involved are not well understood. This study explored the involvement of microglial mitophagy via HBO relative to neuropathic pain therapy.Materials and methodsA total of 80 male Sprague Dawley rats were randomly divided into two groups: a normal group (n = 40) and a mitophagy inhibitor group (n = 40) in which the mitophagy inhibitor cyclosporin A (CsA) was administrated prior to chronic constriction inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…At the cellular and subcellular levels, HBO therapy is known to increase production of reactive oxygen and nitrogen species (RONS), which may account for both beneficial and potentially toxic effects of HBO (Poff et al 2016). Increased production of RONS stimulates expression of genes related to defense against oxidative stress (Matsunami et al 2009), might be involved in induction of mitophagy (Han et al 2017), suppresses MAPK signaling and mitochondrial apoptotic pathway (Niu et al 2013), and could be implicated in stimulation of angiogenesis, proliferation and differentiation of mesenchymal stem cells (Lin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular and subcellular levels, HBO therapy is known to increase production of reactive oxygen and nitrogen species (RONS), which may account for both beneficial and potentially toxic effects of HBO (Poff et al 2016). Increased production of RONS stimulates expression of genes related to defense against oxidative stress (Matsunami et al 2009), might be involved in induction of mitophagy (Han et al 2017), suppresses MAPK signaling and mitochondrial apoptotic pathway (Niu et al 2013), and could be implicated in stimulation of angiogenesis, proliferation and differentiation of mesenchymal stem cells (Lin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HBO promotes capillary regeneration and improves microcirculation. Our previous study tested HBO in rats with induced mitophagy in NP [3]. As expected, HBO reduced the pain behavior test and maintained nerve function because HBO increased mitophagy, which was significantly related to the dephosphorylated LC3-interacting region (LIR) motif of FUNDC1.…”
Section: Discussionmentioning
confidence: 62%
“…Our previous study showed that the analgesic effect of HBO on NP is associated with mitophagy in rats [3]. In the present study, we investigated the molecular mechanism of the mitophagic effect of HBO.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations